PUTTING IT TOGETHER: ALBERT CAMUS, MICHEL FOUCAULT AND AN ETHICS OF THE SELF - Geoffrey Parkes (University of Bucharest Review. Literary and Cultural Studies Series, 2022)
Throughout modernity, the postmodern, and its aftermath, the self, its forms of existence and its very existence have been questioned. But what if, as Jonathan Dollimore writes, “the neuroses, anxiety and alienation associated with the self in crisis are not as much the consequences of its recent breakdown as the very stuff of its creation, and of the culture – Western European Culture – which is sustains?” And what if we review the works of Albert Camus and Michel Foucault in this context, analysing their works as both works on the self (oeuvre) and works on their selves (travailler)? What are the parallels between these dissimilar icons of post-Holocaust French thought and how might their being read together aid our understanding of what it means to craft an ethics of the self?This paper draws on my research into the possibilities of a post-Holocaust ethics of the self, using two writers whose work has been marginalised in the “turn to ethics”. By viewing their work in relation to events of their own time and their engagement with debates about the self, we see their importance in contemporary discussions and the value of their self-reflexive action and radical scepticism in crafting our selves.